Experimental apparatus and methods for synthesizing 1D single-atom array - K. Srakaew (2020)
© Published under licence by IOP Publishing Ltd. We present apparatus and methods for laser cooling and trapping of single rubidium-85 atoms. The setup consists of a magneto-optical trap and identical optical microtraps lined up by using a programmable acousto-optic defector. The apparatus designs and systematic arrangement are described in conjunction with the limitations of the techniques and the scope for future improvement. Individual control over the position and power of each trap attained in our work is the key to addressable and scalable quantum system.